Odpowiedzi

Najlepsza Odpowiedź!
2009-09-07T18:48:18+02:00
A)1⅞ × (-6)=15/8*(-6)= 90/8=11,1/4
b)-1¾ × 8=-7/4*8=14
c)1¹/₃ × 0,5=4/3*1/2=4/6=2/3
d)-1,5:(-2¹/₃)=-1,1/2:(-7/2)=-3/2*(-2/7)=6/14
e)-2⅜-¹/₁₂=-19/8-1/12=-57/24-2/24=-59/24=-2,1/24
f)-0,75-(1⅖)=-3/4-1,2/5=-15/20-1,8/20=-15/20-28/20=-43/20=2,3/20
2009-09-07T18:48:43+02:00
A)-11 1/4
b)14
c)2/3
d)9/14
e)-2 11/24
f)-2 3/20
2009-09-07T18:53:02+02:00
A) ¹⁵/₈*(-6)=-⁴⁵/₄=-11¼
b) - 1¾*8=-⁷/₄*8=-14
c) 1⅓*½=⁴/₃*½=⅔
d) -1½ : (-2⅓) –³/₂*(-³/₅) =⁹/₁₀
e) –2⅜ – ¹/₁₂=¹⁹/₈-¹/₁₂=⁵⁴/₄₈-⁴/₄₈=⁵⁰/₄₈=1²/₄₈= 1¹/₂₄
f) –¾-1⅖=-¾-⁷/₅=-¹⁵/₂₀-²⁸/₂₀=-⁴³/₂₀=-2³/₂₀